2017
DOI: 10.1080/01402382.2017.1300472
|View full text |Cite
|
Sign up to set email alerts
|

Responsive to whom? A comparison of the Mitterrand and Hollande presidencies

Abstract: This article was presented during the workshop on electoral coalitions and their analytical implications at the European University Institute, 13-14 June 2016. We would like to thank the participants for their constructive feedback. We would also like to thank three anonymous reviewers for their helpful comments and suggestions. Of course, any errors remain our own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 34 publications
(24 reference statements)
1
20
0
Order By: Relevance
“…As already discussed in our and other related studies (Damhuis and Karremans 2017; Huber and Stephens 2015; Gingrich and Häusermann 2015), the restrictive policy attitude emerging from the justifications is for a considerable extent in line with the post-industrial ideological profile of the PS. However, the characteristics of the responsible justifications found in the budget speeches also reveal another side of this same story.…”
Section: Results: the Balance Between Responsive And Responsible Justsupporting
confidence: 78%
See 4 more Smart Citations
“…As already discussed in our and other related studies (Damhuis and Karremans 2017; Huber and Stephens 2015; Gingrich and Häusermann 2015), the restrictive policy attitude emerging from the justifications is for a considerable extent in line with the post-industrial ideological profile of the PS. However, the characteristics of the responsible justifications found in the budget speeches also reveal another side of this same story.…”
Section: Results: the Balance Between Responsive And Responsible Justsupporting
confidence: 78%
“…The former (rows 1.1-1.31 in the Appendix) constitute the justifications that we label 'responsive'. These have been extensively examined in our previous study (Damhuis and Karremans 2017), wherein we identified significant overtime changes in the representativeness of the Parti Socialiste, which are largely in line with the programmatic transformation of various European social-democratic between the 1990s and 2000s (e.g. Kitschelt 1994;Green Pedersen & Van Kersbergen 2002).…”
Section: Responsive Vs Responsible Justificationsmentioning
confidence: 76%
See 3 more Smart Citations